Transition to green industry and recycling in a heterogeneous-industry and endogenous growth model - Riku Watanabe (Osaka University, Institute of Social and Economic Research (ISER), 2025)
This study incorporates two heterogeneous industries into an endogenous growth model within the framework of a circular economy. In the model, industries are classified as either brown or green, and each can transition between states through R&D activities related to innovation and greening. Greening R&D is conducted exclusively by firms in the brown industry and enables the transition to the green industry. We analyze the effects of subsidies for greening R&D and show that such subsidies increases labor allocation to both innovation and greening R&D. As a result, the model yields win-win outcome: economic growth is promoted not only by productivity-driven growth acceleration but also by a decline in the share of brown industries that rely on exhaustible resources, which mitigates the negative impact of resource depletion on growth. These findings suggest that advancing a circular economy can be compatible with sustained economic growth.
Keywords: O31; O44; Q53; 330; Endogenous growth; Circular economy; Recycling; Heterogeneous-industry model